Effect of calcium ionophore (A23187) on embryo development and its safety in PGT cycles - Zhang, Junya; Yao, Guidong; Zhang, Tongwei; Hu, Jingyi; Yang, Guang; He, Jiahuan; He, Qina; Fan, Huiying; Bai, Yucheng; Sun, Yingpu (Frontiers in Endocrinology, 2023)
Intracytoplasmic sperm injection (ICSI) has tremendous advantages for resolving the problem of male infertility. However, ICSI fertilization can fail in some patients because of various reasons, primarily because of the failure of egg activation. Oocytes have been activated using calcium ionophore (A23187) in previous clinical cases of ICSI fertilization failure. However, studies on the efficiency of A23187 activation, its effects on the developmental potential of embryos, and its effects on pregnancy outcomes after embryo transfer are relatively limited. In this study, we investigated the safety and long-term efficacy of A23187 by analyzing its effects on fertilization, embryonic development, aneuploidy, and pregnancy outcomes in patients undergoing preimplantation genetic testing (PGT) cycles. Comparative analyses of the activation followed by PGT (A-PGT) and PGT groups revealed no significant differences between the source oocyte cleavage rate and high-quality embryo rate (98.19% vs. 98.63% and 63.13% vs. 68.39%, respectively, p > 0.05). Although the blastocyst formation rate was significantly lower in the A-PGT group than that in the PGT group (52.22% vs. 59.90%, p < 0.05), no significant difference was observed in the blastocyst aneuploidy rates of the two groups (24.49% vs. 24.55%, p > 0.05). Furthermore, no significant differences were observed between the two groups in terms of the live birth rate (43.75% vs. 52.99%), week of delivery, and birth weight of the infants after transfer of euploid blastocysts (p > 0.05). Furthermore, the 2PN rate, egg cleavage rate, blastocyst formation rate, and live birth rate were found to be significantly lower in the A-ICSI group than those in the ICSI group (p < 0.01), but there was no significant difference between the two groups in the week of delivery and birth weight of live births (p > 0.05). These results suggest that the use of A23187 activation as an option in cases of ICSI fertilization failure does not affect the ploidy of developing blastocysts and has no significant effects on the week of delivery or birth weight after transfer. Thus, we provide a scientific basis for the clinical safety of oocyte activation using A23187.